#100: Disseminated Toxoplasmosis Presenting as Persistent Fevers in a Hematopoietic Stem Cell Transplant Recipient. (26th March 2021) - Khan, A; Nadimpalli, S; Gans, H
Abstract: Background: Toxoplasma reactivation is a known concern in hematopoietic stem cell transplant (HSCT) patients with high mortality of approximately 40% and up to 100% if left untreated. The risk is highest when patients are most immunocompromised and presentation can vary from isolated fever to disseminated disease with CNS toxoplasmosis, pneumonitis, and myocarditis. Case: The patient is a 10-year-old male with acute promyelocytic leukemia (APML) CNS1 status post-chemotherapy, secondary acute myeloid leukemia (AML), now status post 10/10 matched unrelated donor hematopoietic stem cell transplant (HSCT). He initially developed fever and neutropenia during conditioning chemotherapy with resolved fever prior to stem cell transplant. His transplant course was complicated by grade IV mucositis on day +4 with improvement on day +11. On day +19 he developed new fevers (Tmax 40.5 o C) with a negative initial workup. He continued to have persistent fevers on broad-spectrum empiric therapy with meropenem and liposomal amphotericin B and also complained of daily headaches and abdominal pain, with worsening diffuse body pain. On day +26 the Pediatric Infectious Diseases team was consulted as a CT Chest demonstrated small scattered ground glass nodules in the right lung with minimal bibasilar atelectasis and small pleural effusions. Upon chart review, he was noted to be Toxoplasma IgG positive prior to transplant. Further infectious diseases studies were sent to evaluate for fungal etiologies, including a Toxoplasma PCR blood, and given persistent fever, he was empirically started on trimethoprim–sulfamethoxazole (TMP-SMX) by the primary team. Shortly after the initiation of TMP-SMX he became afebrile and testing confirmed Toxoplasma reactivation with positive PCR studies from the blood, cerebrospinal fluid (CSF), bronchoalveolar lavage (BAL), and bone marrow. He was treated with pyrimethamine, sulfadiazine, and folinic acid and developed sulfa crystalluria, requiring alteration of his therapy. He received multiple treatment regimens and continued on maintenance therapy without further complications. Conclusion: This case highlights the importance of serial surveillance or empiric prophylaxis for Toxoplasma reactivation in HSCT recipients known to have prior infection. There is high associated mortality and patients may present with isolated fever or severe disseminated disease with multi-organ involvement. Toxoplasma disease requires the presence of organ involvement as demonstrated in our patient and treatment is typically 6 weeks at higher doses followed by maintenance therapy. The definite treatment course varies by clinical response and multiple options are available if toxicities occur.